The Effectiveness of Mindfulness Training on the Experience of Music Performance Anxiety in Young Adult Musicians. A Preliminary Investigation - Stanson, Nicole; Comeau, Gilles; Smith, Andra; Swirp, Mikael (Revue musicale OICRM, 2022)
Research has shown that music performance anxiety (mpa) is experienced by individuals of all ages and skill levels. Due to the need for effective management of performance anxiety in musicians, researchers have begun to investigate the viability of mindfulness, which has been proven as an effective treatment in populations with generalized anxiety. This study assessed the effects of a two-week mindfulness intervention on musicians before and after a performance, using the State component of the State-Trait Anxiety Inventory (stai) and the Revised Kenny Music Performance Anxiety Inventory (kmpai-r). Results from this study suggest that mindfulness has a significantly positive effect on state anxiety in music performance, and that a two-week mindfulness training intervention model should be investigated further as a potential intervention to reduce mpa.